2020
DOI: 10.3390/pharmaceutics12080775
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Fibrosis Following Ischemia/Reperfusion Injury in Rodents Utilizing Na Magnetic Resonance Imaging

Abstract: Fibrosis is often heterogeneously distributed, and classical biopsies do not reflect this. Noninvasive methods for renal fibrosis have been developed to follow chronic kidney diseases (CKD) and to monitor anti-fibrotic therapy. In this study, we combined two approaches to assess fibrosis regression following renal ischemia-reperfusion injury (IRI): magnetic resonance imaging (MRI) and noninvasive extracellular matrix (ECM) biomarkers. MRI was used to evaluate fibrosis in bilateral IRI in rats after reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our findings of a decreased sodium cortico‐medullary gradient and correlations between 23 Na‐MRI and skGFR and fibrosis in IRI, but not in UUO, are somewhat in accordance with a previous study conducted by Nielsen et al 27 Their data suggested a decreased gradient after 7 days of IRI, but, unlike us, they also observed a decrease of the gradient in UUO rats. However, these changes were normalized on day 14 and day 21 after reperfusion, corresponding to no significant changes in fibrosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings of a decreased sodium cortico‐medullary gradient and correlations between 23 Na‐MRI and skGFR and fibrosis in IRI, but not in UUO, are somewhat in accordance with a previous study conducted by Nielsen et al 27 Their data suggested a decreased gradient after 7 days of IRI, but, unlike us, they also observed a decrease of the gradient in UUO rats. However, these changes were normalized on day 14 and day 21 after reperfusion, corresponding to no significant changes in fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the study found a positive correlation between fibrosis and total 23 Na-MRI signal, probably because of necrosis, resulting in increased extracellular matrix for sodium distribution, although no correlation was found between fibrosis and the corticomedullary sodium gradient. 27 We found a negative correlation between fibrosis and the 23 Na medulla/cortex ratio in IRI, but not in UUO. Combined, the observed differences in UUO are probably a result of the cortical thinning and associated uncertainties observed in this model.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In addition, it may steer interstitial fibrosis or renal tubular atrophy. The pathogenesis of RHR injury consists of apoptosis, endothelial dysfunction, immune system activation, and transcriptional alternation. , The hypoxic microenvironment forces cells to switch to anaerobic respiration, resulting in lactate formation due to a drop in adenosine triphosphate production. Moreover, intracellular ionic imbalance results in the generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%